Penerapan Model Terdistribusi untuk Sistem Smarthome Menggunakan Multi-Sensor Berbasis Internet of Things (IoT) - Samratul Fuady; Ulfa Khaira; Yosi Riduas Hais; Robertus Herodian Sitanggang (Journal of Electrical Power Control and Automation (JEPCA), 2021)
The use of smarthome technology to monitor and control homes is growing recently. The smarthome system requires the integration of several sensors to determine the conditions in the house. In a centralized smarthome system, all sensors are connected to a single node to perform data processing and communication which can result in system failure if this node is broken. In this study, we use a distributed model for the smarthome system. The designed system consists of three nodes, which are kitchen instrument, room instrument, and door instrument. These three instruments are equipped with RFID sensors, temperature sensors, gas sensors, and reed switch sensors to perform security features of the smarthome that can be accessed remotely via smartphones or computers. The results show that the system has been able to work well and can overcome the problem of failure on some instruments without causing the whole system to collapse. This smarthome system has an average delay of 2.21 seconds.